Fill-in-the-blank Recurrence Exercises

  1. Find a closed form solution for recurrence S below:
    S(1) = 3
    S(n) = 5 + S(n-1)
    
    Expand:
    S(n) = 5 + S(n-1)
       
         = 5 + (____________________________________) (expand)
    
    
         = _____________________________________________ (expand again)  
    
    
    General form: _________________________________________________.
    
    
    To get the S term to the base case, let k = ___________________.  This gives
    
    
    ____________________________________________________________________________
    
    which is the guess.
    
    Verify that given the definition for S above, S(n) = _______________________.
    Base case (n=1): _______________________________________
    
    Inductive Step: (Hint: If the guess holds for k, it also holds for k+1.  Write this out mathematically using the actual guess.)
    
    _______________________________________________________________________________.
    
    Proof:
    By the definition of S, S(k+1) = _____________________________________________.
    
    By the inductive hypothesis, _________________________________________________.
    
    Substituting into line 1, this gives S(k+1) =  _______________________________
    
    = (simplify) ______________________________________________________________________________.
    





















  2. Find a closed form solution for recurrence T below:
    T(1) = 6
    T(n) = 4 + T(n/2)
    
    Expand:
    T(n) = 4 + T(n/2)
       
         = 4 + (_________________________________________) (expand)
    
    
         = ______________________________________________ (expand again)
    
    
    General form: _________________________________________________.
    
    
    To get the T term to the base case, let k = ___________________.  This gives
    
    
    ____________________________________________________________________________
    
    which is the guess.
    
    Verify that given the definition for T above, T(n) = _______________________.
    Base case (n=1): _______________________________________
    
    Inductive Step: (Hint: If the guess holds for all values between 1 and k, 
    it also holds for k+1.  Write this out mathematically using the actual guess.)
    
    
    _______________________________________________________________________________.
    
    Proof:
    By the definition of T, T(k+1) = _____________________________________________.
    
    
    By the inductive hypothesis, _________________________________________________.
    
    Substituting into line 1, this gives T(k+1) =  _______________________________
    
    
    = (simplify) ______________________________________________________________________________.